Micro-Electromechanical Acoustic Resonator Coated with Polyethyleneimine Nanofibers for the Detection of Formaldehyde Vapor - Da Chen; Lei Yang; Wenhua Yu; Maozeng Wu; Wei Wang; Hongfei Wang (Micromachines, 2018)
We demonstrate a promising strategy to combine the micro-electromechanical film bulk acoustic resonator and the nanostructured sensitive fibers for the detection of low-concentration formaldehyde vapor. The polyethyleneimine nanofibers were directly deposited on the resonator surface by a simple electrospinning method. The film bulk acoustic resonator working at 4.4 GHz acted as a sensitive mass loading platform and the three-dimensional structure of nanofibers provided a large specific surface area for vapor adsorption and diffusion. The ultra-small mass change induced by the absorption of formaldehyde molecules onto the amine groups in polyethyleneimine was detected by measuring the frequency downshift of the film bulk acoustic resonator. The proposed sensor exhibits a fast, reversible and linear response towards formaldehyde vapor with an excellent selectivity. The gas sensitivity and the detection limit were 1.216 kHz/ppb and 37 ppb, respectively. The study offers a great potential for developing sensitive, fast-response and portable sensors for the detection of indoor air pollutions.